Meninos e meninas de Deus: a experiência de ressocialização de adolescentes em conflito com a lei na comunidade Santa Filomena em Fortaleza-CE - Silva, Zilmara Alves da (2022)
Issues regarding to adolescents in conflict with the law have given rise to many studies and researches as social concern about the subject increases, which is current and relevant throughout the country. Such problems and issues do not exist autonomously, nor in the same way for those involved or in the different spheres of life which they appear. This research, based on a critical approach, aims to make visible and analyze the social and intersectional asymmetries (gender, class and race) built in the process of resocialization, resignification of the socio-affective relationships of the adolescents of the second group of Meninos de Deus, from the Santa Filomena community, in Fortaleza/CE, giving special attention to girls, with a view to expanding the rights and citizenship of these adolescents inserted in a context of daily violence. It discusses criminality, the codes valued differently in relation to the categories established among adolescents who committed infractions and fulfilled socio-educational measures. Methodologically, it is a qualitative research that seeks to describe and analyze the culture and human behavior of a group from the point of view of those being studied; It is based in bibliographic, documentary and oral sources through semi-structured interviews carried out individually, either face-to-face or virtual (through Google's Meet platform). The target audience is made up of seventeen people, fifteen young people from the second group of the Meninos e Meninas de Deus group and two members of the project operationalization team, residents or former residents of the Santa Filomena community, taking into account the gender issue. The lives of adolescents in conflict with the law are constitutive of the center of the contemporary social problem and, almost always, are already closely linked (or being strictly managed) by assistance, family, religious, mercantile and work dynamics that, in most cases, cases, are inscribed in what is called, in the peripheries, the 'world of crime'. Adolescents, in conflict with the law, have been highlighted in the statistics of crimes reported by the local and national media, which justifies the growing scientific visibility, however, studies involving girls are still rare, since they represent a smaller number. in national statistics. This fact has created the invisibility of the girls' action profile, which makes it difficult to know their reality and, consequently, to create more appropriate actions for the female universe. The social processes that involve this audience need to be more effectively on contemporary agendas.